Petrography and Geochemistry of Metasedimentary Rocks from the Taku Schist in Kelantan, North-East Peninsular Malaysia. - Muhammad Irman Khalif bin Ahmad Aminuddin; Nugroho Imam Setiawan; I Wayan Warmada; Kamar Shah Ariffin; Kotaro Yonezu (Geological Engineering Department Universitas Gadjah Mada, 2021)
The Taku Schist, which is located in the north-east Peninsular Malaysia, is characterized by its North-South oriented elongated body. It forms part of the Indonesian orogenic build-up that was generated via the convergence of the Sibumasu continental unit and Sukhothai Arc. Subsequent petrography analyses of the metasedimentary rocks sourced from the Taku Schist revealed that their formation was attributable to the metamorphism of greenschist into amphibolite facies, which could be observed near the Triassic and Cretaceous intrusions of the Kemahang Granite. The evolutionary process of the rocks could be linked with the interactions occurring between contact and regional metamorphisms. The resulting chemical classification upon their assessment disclosed that the metasedimentary rocks of Taku Schist were made up of greywacke and shale, grouped into the quartzose sedimentary provenance, and belonged to the Continental Island Arc (CIA). This information is required for the tectonic setting discrimination purpose. It is a reflection of the episodic contractions underwent by the Taku Schist, wherein they would lead to the Sibumasu sedimentary cover along with both an accretionary wedge and the genetically-correlated Bentong-Raub melange to different greenschist. Otherwise associated with amphibolite facies, the conditions and depths of the facies were determined according to their position in relation to the upper plate of the Sukhothai Arc.